Globalization and political economy of food policies: Insights from planting restrictions in colonial wine markets - Meloni, Giulia; Swinnen, Johan (Wiley, 2022)
Globalization transforms not just the economics of production and exchange in the world, but also the political economy of public policies. We analyze how wine regulations, and more specifically planting rights restrictions, have been affected by globalization. We study colonial expansions of wine producing empires and find that (a) planting right restrictions and compulsory uprooting of vineyards are introduced to deal with falling wine prices as colonial wine production takes off and expands; (b) that enforcement of the restrictions and uprooting was difficult and often imperfect; and (c) that there was a strong persistence of the policies: after their introduction, the restrictions remain in place for a long time (often centuries) and they are only removed after major shocks to the political economy equilibrium.